Pengaruh Kinerja Pegawai Terhadap Kepuasan Masyarakat di Dinas Penanaman Modal dan Pelayanan Satu Pintu Kabupaten Gorontalo - Taufiq, Rahmat; Aneta, Asna; Sulila, Ismet (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research is entitled "The influence of employee performance on community satisfaction at the One Stop Integrated Services and Investment Service of Gorontalo Regency" and is under the guidance of Prof. Dr. Asna Aneta, M.Si, as supervisor I and Mr. Dr. Ismet Sulila S.E, M.Si, as supervisor II. This research aims to find out whether there is an influence of employee performance on community satisfaction at the Gorontalo Regency One Stop Investment and Integrated Services Service in terms of employee performance in providing services to the community. This research uses quantitative methods using simple regression analysis, the sample used was 96 respondents. From the calculation of hypothesis testing (t test) it can be seen that the t-calculated value of the results which describes "The Influence of Employee Performance on Community Satisfaction in the One Stop Investment and Integrated Services Service of Gorontalo Regency" is 18.091, then this value is consulted with the t-table, with N = 96 with a significance level of 5% or 0.05, it is known that the t-table value is 1.66123. So, the hypothesis which states that "there is an influence of employee performance on community satisfaction in the Gorontalo Regency One Stop Investment and Integrated Services Service" can be said to be accepted.